2020
DOI: 10.1177/0954008320951610
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of hybrid cyanate ester resin in the presence of polysilazane and its properties

Abstract: A hybrid cyanate ester resin containing polysilazane was prepared via the prepolymerization of bisphenol-A dicyanate ester monomer (BADCy) in the presence of polysilazane (PSZ) under low temperature conditions in a short period of time. Fourier transform-infrared (FT-IR) spectroscopy and nuclear magnetic resonance (NMR) spectroscopy reveal that the polymerization reaction of BADCy can be carried out in the presence of PSZ to obtain a hybrid resin below 100°C and polymethylsilazane (PHS) exhibits an improved pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Polysilazane supplied by our laboratory, 44 which was prepared from methyl vinyl dichlorosilane and vinyl trichlorosilane via an ammonolysis method (Figure S1). 45,46 Phenolic resin was acquired from Shanghai Aladdin Biochemical Technology Co., Ltd., diisopropylbenzene peroxide (DCP) was obtained from Shanghai Lingfeng Chemical Reagent Co., Ltd., dimethylformamide (DMF) was purchased from Shanghai McLean Biochemical Technology Co., Ltd., and dioxane was obtained from Shanghai Titan Technology Co., Ltd. All raw materials were used as received without any further purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polysilazane supplied by our laboratory, 44 which was prepared from methyl vinyl dichlorosilane and vinyl trichlorosilane via an ammonolysis method (Figure S1). 45,46 Phenolic resin was acquired from Shanghai Aladdin Biochemical Technology Co., Ltd., diisopropylbenzene peroxide (DCP) was obtained from Shanghai Lingfeng Chemical Reagent Co., Ltd., dimethylformamide (DMF) was purchased from Shanghai McLean Biochemical Technology Co., Ltd., and dioxane was obtained from Shanghai Titan Technology Co., Ltd. All raw materials were used as received without any further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Polysilazane supplied by our laboratory, 44 which was prepared from methyl vinyl dichlorosilane and vinyl trichlorosilane via an ammonolysis method (Figure S1). 45,46…”
Section: Methodsmentioning
confidence: 99%
“…Recently, many scholars have been committed to studying how to cure cyanate at low temperature for a short time. [10][11][12][13][14][15] Endo et al investigated the reaction of aliphatic amines and cyanate esters at low temperature and confirmed the formation of intermediates during the reaction based on NMR and FT-IR spectroscopy. Wang et al found that benzoxazine and cyanate gel after 24 h at 30°C in solution and proposed a catalytic mechanism for the polymerization of cyanate by the tertiary amines in benzoxazine.…”
Section: Introductionmentioning
confidence: 99%
“…As a high performance resin, CE resins are widely used in high performance radome, electronic packaging materials, aerospace industry, and other fields due to their excellent thermal properties, dielectric properties, flame retardancy, and low water absorption 1,2 . However, CE resin has a fatal defect in that the curing temperature is very high, above 300°C, which cannot meet the industrial demands 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…As a high performance resin, CE resins are widely used in high performance radome, electronic packaging materials, aerospace industry, and other fields due to their excellent thermal properties, dielectric properties, flame retardancy, and low water absorption. 1,2 However, CE resin has a fatal defect in that the curing temperature is very high, above 300 C, which cannot meet the industrial demands. 3,4 At the same time, due to the highly symmetrical structure of the triazine ring produced by the trimerization reaction of CE resin, the CE resin not only has a large volume shrinkage but also exhibits brittleness, which seriously affects the application of the CE resin in various fields.…”
Section: Introductionmentioning
confidence: 99%